APAKAH MODAL INTELEKTUAL MEMPENGARUHI KINERJA ORGANISASI DI SEKTOR PUBLIK INDONESIA? - Harsoyo, Allamanda Titania; Mabrur, Azas (Politeknik Keuangan Negara STAN, 2025)
This study aims to examine the effect of intellectual capital on organizational performance within the Ministry of Agrarian and Spatial Planning/National Land Agency (ATR/BPN). Data were collected through a structured online questionnaire distributed to 112 civil servants using a simple random sampling technique. The data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method to test the relationship between five dimensions of intellectual capital and organizational performance. The findings reveal that public organizational, social, technological, and relational capital have a significant positive effect on organizational performance, while public human capital does not show a significant influence. These results imply that strengthening organizational systems, digital transformation, and stakeholder collaboration is more crucial than relying solely on individual competence. The study provides practical guidance for public institutions to optimize knowledge-based resources in achieving effective and accountable governance.